Edith Segal in Detroit: on stage and on the picket line. Issue 3 (2nd September 2021) - Hooper, Colleen
ABSTRACT: Edith Segal reimagined her relationship to her audience and created new methods of performing to support political causes during the three years she lived in Detroit, Michigan. She broke away from the expectations associated with modernist aesthetics championed by New York City dance critics and immersed herself in various roles within the Federal Theatre Project (FTP). In oral history interviews and her own writing, Segal described recruiting interested labor groups to attend the FTP's productions, which in turn created new audiences for theater and bolstered her view of how socially relevant productions could impact audiences. She adapted modern dance movement vocabulary to support theatrical scenarios and worked as part of a production team to communicate the main concepts of several plays. Throughout this process, Segal redefined how modernism could support leftist performance and shifted her focus to the audiences she most wanted to serve.